Experiences of Well-Being in Child-Bearing Women: What Helps and Hinders - Kwee, Janelle; McBride, Hillary; Rossen, Larissa (Canadian Journal of Counselling and Psychotherapy, 2020)
Little research has been done to date to understand, qualitatively, the contributing factors of psychological thriving during pregnancy, birth, and postpartum, particularly from the voices of mothers themselves. In order to better understand what women perceive as contributing to a healthy and positive child-bearing experience, the authors asked postpartum women to report what factors contributed to their well-being. Using the enhanced critical incident technique, women reported what they found was helpful, hindering, or what they would have wished for in their pregnancy, birth, and postpartum experiences. Implications and recommendations for counsellors working with women during pregnancy and the postpartum period are discussed.